GHOST MIGRATION IN PLAYSTORE: MYSTERY REPRODUCTION AND AESTHETIC RESISTANCE - Dwi Susanto (ppjbsip, 2020)
Mystery story genre, such as ghost story, have migrated in virtual media or digital media, exspecially Playstore. The migration caused many modifications and adptation, that convert with digital media. This paper aims to show ghost story in Playstore aplication, the response reader, and the ghost story as aesthetic discourse pratical. The data of this paper are ghost stories in Playstore, response readers,and narartion which is related with aesthetic discourse. The interpretation data use sosiological perspective. This paper result that the ghost story migration in virtual media have changed image and representation ghost stories became metropolit. It changes the oppsite between tradition versus modern. The response reader appears that this genre is habitual and popular in thier horizon expecation as information and entertaiment. The simbolic reproduction show that the mystery world create pleasure, entertaiment, and other mystery. It is resistance toward canonical aesthetic and mystery genre itself, which eliminated by dominan aesthetic.AbstrakGenre cerita misteri, seperti cerita hantu, telah bermigrasi di media virtual atau media digital, khususnya Playstore. Migrasi tersebut menyebabkan banyak modifikasi dan adptasi, yang dikonversi dengan media digital. Makalah ini bertujuan untuk menunjukkan cerita hantu dalam aplikasi Playstore, respons pembaca, dan cerita hantu sebagai wacana estetika yang praktis. Data dari makalah ini adalah cerita hantu di Playstore, respons pembaca, dan narartion yang terkait dengan wacana estetika. Data interpretasi menggunakan perspektif sosiologis. Makalah ini menghasilkan bahwa migrasi cerita hantu di media virtual telah mengubah gambar dan representasi cerita hantu menjadi metropolitan. Ini mengubah oppsite antara tradisi versus modern. Melalui respons pembaca terlihat bahwa genre ini adalah kebiasaan dan populer dalam harapan cakrawala mereka sebagai informasi dan hiburan. Reproduksi simbolik menunjukkan bahwa dunia misteri menciptakan kesenangan, hiburan, dan misteri lainnya. Ini adalah perlawanan terhadap estetika kanonik dan genre misteri itu sendir, yang dihilangkan oleh estetika dominan.